IMPLEMENTASI SHUTTLE TIME TERPADU DALAM PEMASSALAN DAN PENGEMBANGAN OLAHRAGA BULUTANGKIS - Donie Donie; Irfan Arifianto; Hermanzoni Hermanzoni; Roma Irawan; Eval Edmizal; Vega Soniawan; Yogi Setiawan (Universitas PGRI Palembang, 2019)
Badminton sport coaching which tends to be instant causes a gap between athletes' achievements in Sijunjung Regency and sports activities for potential athletes of elementary school age. A program is needed that can socialize badminton among elementary school students that is able to foster interest and motivation to play badminton and form a coaching forum into the badminton coaching club. The integrated Shuttle Time program is an effort to socialize and increase interest in playing badminton in elementary school students in general in Sijunjung Regency. The partner in this activity is Ikatan Sarjana Olahraga (ISORI) the Sijunjung Regency. The key to implementing badminton with Shuttle Time is to provide badminton lessons that are cheaper, more interesting, fun and safe for elementary school students. The method used in this activity is through several stages, namely the first stage of direct field observation and coordination with related parties in this activity. The second stage provides Shuttle Time training for elementary school sports teachers and the third stage the teacher implements the shuttle time for students. The result of this activity is that the training activities will be carried out for 3 days and the teacher will get provisions in implementing this shuttle time in learning badminton in class hours and extracurricular development activities.Popularize and Development, Badminton Shuttle Time